1998
DOI: 10.5032/jae.1998.01048
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles Facing Extension Agents in the Development and Delivery of Extension Educational Programs for Adult Farmers in the Province of Esfahan, Iran

Abstract: The purpose of this study was to assess the viewpoints of extension agents regarding the most appropriate methods for teaching adult fanners, their own educa tional needs, and obstacles hampering them in developing and delivering educational programs for adult fanners in Esfahan Province, Iran. The population included all extension agents in the province of Esfahan who were involved in teaching processes andpractices to adult fanners (N=102).. Data were collected through a questionnaire mailed to each extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 3 publications
(6 reference statements)
3
16
0
Order By: Relevance
“…Many other researchers have also focused on the aims and roles of AES in the light of agricultural development of Iran and have reported similar findings (Beygi, Zarafshani & Chizari, 2000;Chizari, Karbasioun, & Lindner, 1998;Darvishi, 2003;Heidari, 2000;Karami, 1995Karami, , 2001Karbasioun & Chizari, 2004;Lotfi, 2004;Ministry of Jahad-e-Keshavarzi, 2002;Pezeshki-Raad & Aghai, 2002;PezeshkiRaad, Aghai, & Ukaga, 2001;Zarafshani, 2002). Most of these studies, however, have concentrated on the support provided by AES to farmers in the past and not on the support that should be provided in the future.…”
Section: Theoretical Frameworksupporting
confidence: 55%
“…Many other researchers have also focused on the aims and roles of AES in the light of agricultural development of Iran and have reported similar findings (Beygi, Zarafshani & Chizari, 2000;Chizari, Karbasioun, & Lindner, 1998;Darvishi, 2003;Heidari, 2000;Karami, 1995Karami, , 2001Karbasioun & Chizari, 2004;Lotfi, 2004;Ministry of Jahad-e-Keshavarzi, 2002;Pezeshki-Raad & Aghai, 2002;PezeshkiRaad, Aghai, & Ukaga, 2001;Zarafshani, 2002). Most of these studies, however, have concentrated on the support provided by AES to farmers in the past and not on the support that should be provided in the future.…”
Section: Theoretical Frameworksupporting
confidence: 55%
“…Iran is also dependent on pesticide and insecticide imports. The goal of self-sufficiency in Iran has been the focus of recent research (Chizari, Karbasioun, & Lindner, 1998;Chizari, Pishbin, & Lindner, 1997;Chizari, Lindner, & Bashardoost, 1997;Pezeshki-Raad, Yoder, & Diamond, 1994). Extension agents have played an important role in helping agriculture systems overcome many problems.…”
Section: Journal Of Agricultural Education 20mentioning
confidence: 99%
“…These authors state further that to ensure Extension agents are well trained, extension management must determine training needs to increase agent capabilities. Similarly Chizari, Karbasioun, and Lindner (1998) noted that Extension will be seriously limited in its ability to plan and execute effective educational programs and other technology transfer activities, without an adequate number of well-trained agents.…”
Section: Journal Of Agricultural Education 20mentioning
confidence: 99%
“…A gap between what and how information is being offered and what and how farmers wish to receive information exists. Numerous studies have identified to desire of Iranian farmers to be more involved in agriculturally based training and development programs (Chizari, Lindner, & Noorbadi, 2000;Chizari, Lindner, & Zoghie, 1999;Chizari, Karbasioun, & Lindner, 1998). A continued and sustained effort is needed to ensure participatory approaches to education and training are achieved.…”
Section: Conclusion and Discussionmentioning
confidence: 99%